2013
DOI: 10.15560/9.5.1057
|View full text |Cite
|
Sign up to set email alerts
|

Geographic note on species of the genus Upa Kimsey, 1991 (Hymenoptera: Tiphiidae, Thynninae) in the Atlantic Forest, Brazil

Abstract: Upa Kimsey is a poorly known genus of Tiphiidae with seven species. This genus has records in forest areas and in this paper we present new records to four species. All specimens were collected by malaise traps in four areas of Atlantic Rain Forest and three of Atlantic Semi-deciduous forest, mainly from high and mid-elevations. The new records indicate that species of Upa are not as rare as others genera of Tiphiidae, which are virtually unknown in many Neotropical regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The BAR has experienced massive habitat loss with expansion of the agricultural landscapes and monocultural exploration, making this habitat a global priority for biodiversity conservation (Ribeiro et al 2011). Recently, new records for Upa Kimsey, 1991 (Tiphiidae, Thynninae) were found in the same areas of SAF, in Barretos, Matão and União Paulista (Justino et al 2013), which reinforces that poor sampling of Thynninae in these areas may be a reason for the current observed distribution. An ecological study of Tiphiidae from the BAR (Justino et al 2016) showed that even in areas with enormous fragmentation, such as the SAF, there are many species yet to be recorded and discovered.…”
Section: Discussionmentioning
confidence: 72%
“…The BAR has experienced massive habitat loss with expansion of the agricultural landscapes and monocultural exploration, making this habitat a global priority for biodiversity conservation (Ribeiro et al 2011). Recently, new records for Upa Kimsey, 1991 (Tiphiidae, Thynninae) were found in the same areas of SAF, in Barretos, Matão and União Paulista (Justino et al 2013), which reinforces that poor sampling of Thynninae in these areas may be a reason for the current observed distribution. An ecological study of Tiphiidae from the BAR (Justino et al 2016) showed that even in areas with enormous fragmentation, such as the SAF, there are many species yet to be recorded and discovered.…”
Section: Discussionmentioning
confidence: 72%